The Conflicting Patterns In The Novel Of Menna,kiyamat Chatat Essahraa. Cultural Reading - dehliz, Ahmed; khalfallah, Benali (El Omda in Linguistics and Discourse Analysis, 2023)
This study aims to expose the cultural concept in the Algerian novelist's discourse, and the focus has been on the arguments of cultural criticism as a cognitive tool that we rely on in disturbing and undermining the imperialist mind that tends to support hegemony over the marginal format, by exposing the heated relationship between the conflicting systems in the novel from (Menna) by the El-Haj Ahmed Al-Zywani.